’They Lived Happily Ever After’: Ending Contemporary Romantic Comedy - Celestino Deleyto Alcalá (Miscelánea: A Journal of English and American Studies, 1998)
The ideology of romantic comedies has often been located in their attitude to the traditional happy ending: an unproblematic happy ending makes for a film that supports dominant discourses; a problematised one suggests attempts to transgress narrative and cultural conventions. In this essay, I attempt to escape from this inflexible binary logic and propose an analysis of the endings of contemporary romantic comedy which explores the texts’ incorporation of cultural transformations and, more specifically, how the strategies of containment and closure negotiate new attitudes in the realm of romantic and sexual relationships in contemporary US American society. As part of a broader research on contemporary developments in romantic comedy, I sketch here five aspects of romantic relationships in which the endings of recent examples of the genre show awareness of social developments: the lonely romantic hero/-ine, the uneasiness about the durability of the couple, the nostalgia for a more innocent past, the impact of changing gender roles both socially and sexually, and the visibility of different gender permutations in intimate relationships.